2011
DOI: 10.5897/sre10.1059
|View full text |Cite
|
Sign up to set email alerts
|

Enviromental, socio-cultural and economical effects of ecotourism perceived by the local people in the northwestern Turkey: Kiyiky case

Abstract: In the study, examining the ecotourism opportunities in Kiyiköy town of Vize district of Kirklareli province situated on the northwestern Turkey, the awareness of the local people and their roleexpectations in this subject have been determined and the perceptions of the local people towards the environmental, socio-cultural and economical effects of ecotourism have been exposed. In this study, the relationship between socio-cultural and economic impacts and local people support for tourism are examined. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The emergence of ecotourism should be the solution of the effects of environmental damage, as well as improving the welfare of society [34]. People's motivation in mangrove ecosystem management, either aimed at achieving improved welfare or with conservation motivation, should emerge independently to support the development and sustainability of an ecotourism [30,44].…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of ecotourism should be the solution of the effects of environmental damage, as well as improving the welfare of society [34]. People's motivation in mangrove ecosystem management, either aimed at achieving improved welfare or with conservation motivation, should emerge independently to support the development and sustainability of an ecotourism [30,44].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the Annapurna Conservation Area of Nepal, the local community has initiated awareness camps and adult literacy programs, which showcase the transformative potential of community involvement in ecotourism (Bajracharya et al, 2007). As communities gain a deeper understanding of ecotourism principles, there is a noticeable decline in unsustainable activities like hunting, fishing, and deforestation, indicating a positive correlation between community participation and the preservation of the region's socio-cultural identity (Kiper et al, 2011;Reimer & Walter, 2013).…”
Section: Socio-cultural Role Of Community Participation In Ecotourismmentioning
confidence: 99%
“…Results indicated that ARMAX model proves the theory of economics in which demand for international travel has a positive relationship with the income of tourist`s native country. Kiper et al (2011) studied the ecotourism opportunities in Kiyiköy town of Turkey, the awareness of the local people and their role-expectations in this subject have been assessed and the perceptions of the local people towards the environmental, socio-cultural and economic effects of ecotourism have been examined. Results of factor analysis revealed that the area has significant ecotourism potential and the local people have a positive attitude towards ecotourism planning to be developed.…”
Section: Literature Reviewmentioning
confidence: 99%